Partially methylated domains are hypervariable in breast cancer and fuel widespread CpG island hypermethylation - Arie B. Brinkman (Nature Portfolio, 2019)
In cancer, global DNA methylation loss and CpG island hypermethylation are commonly observed. Here, in breast cancer the authors find that hyper-variability of partially methylated domains is the prime source of DNA methylation variation and that these domains fuel CpG island hypermethylation.